MENCEGAH SERANGAN DDOS (DISTRIBUTED DENIAL OF SERVICE) TERHADAP EMAIL SERVER - Mangapul Siahaan (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2021)
An email service provider or email server is a very important application for a company. With the development of information technology and internet crime, there is a possibility of attacks on the email server resulting in dense email server traffic, thus slowing the performance of the email server and disrupting the service to email server users. One of the attacks that occurred was a DDOS (Distributed Denial of Service) attack where the attack paralyzed server performance by sending many packets from various sources of IP addresses to one target. One of the DDoS attacks on the email server is to disable the SMTP, IMAP, POP3 protocols. Prevention of this attack can be done with Fail2ban which can detect unusual activity and perform an automatic block. In this study using the NDLC method, starting from analysis, design, simulation, and implementation. The results obtained by implementing fail2ban to prevent DDoS attacks on email servers can reduce incoming spam by up to 21%.